2018
DOI: 10.1038/s41598-018-22860-2
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of a highly N-glycosylated polypeptide increases the expression of ER-localized proteins in plants

Abstract: Plants represent promising systems for producing various recombinant proteins. One key area of focus for improving this technology is developing methods for producing recombinant proteins at high levels. Many methods have been developed to increase the transcript levels of recombinant genes. However, methods for increasing protein production involving steps downstream of transcription, including translation, have not been fully explored. Here, we investigated the effects of N-glycosylation on protein productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 50 publications
1
29
1
Order By: Relevance
“…The final PCR products were digested with BamHI and XhoI restriction endonucleases and inserted into the plant expression vector 326‐GFP, digested with BamHI and XhoI (Kim et al ., ). The M domain, the N‐terminal fragment from amino acid positions 231 to 290 of human protein tyrosine phosphatase receptor type C (CD45), was fused to the N‐terminus of CBM3‐bdSUMO‐hIL6 by overlapping PCR using plasmid EelepfM (Kang et al ., ) as a template and the primer sets PF‐5, PR‐6, PF‐7 and PR‐8 (Table S1). The plasmid obtained by PCR amplification, named 326 ‐ M‐CBM3‐bdSUMO‐hIL6 , was digested with PstI and EcoRI and inserted into the plant expression binary vector pCAMBIA1300, digested with PstI and EcoRI , to give p1300‐C3bdSU‐hIL6 (Figure a).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The final PCR products were digested with BamHI and XhoI restriction endonucleases and inserted into the plant expression vector 326‐GFP, digested with BamHI and XhoI (Kim et al ., ). The M domain, the N‐terminal fragment from amino acid positions 231 to 290 of human protein tyrosine phosphatase receptor type C (CD45), was fused to the N‐terminus of CBM3‐bdSUMO‐hIL6 by overlapping PCR using plasmid EelepfM (Kang et al ., ) as a template and the primer sets PF‐5, PR‐6, PF‐7 and PR‐8 (Table S1). The plasmid obtained by PCR amplification, named 326 ‐ M‐CBM3‐bdSUMO‐hIL6 , was digested with PstI and EcoRI and inserted into the plant expression binary vector pCAMBIA1300, digested with PstI and EcoRI , to give p1300‐C3bdSU‐hIL6 (Figure a).…”
Section: Methodsmentioning
confidence: 99%
“…A previous study found that the endoplasmic reticulum (ER) accumulates high levels of recombinant proteins (Gomord et al, 1997;Kang et al, 2018;Sohn et al, 2018;Wandelt et al, 1992). Thus, to achieve a high level of expression, we used the BiP leader sequence to target the recombinant protein to the ER.…”
Section: Design Of a Recombinant Gene For High Level Expression In Plmentioning
confidence: 99%
See 1 more Smart Citation
“…The ER localization renders recombinant proteins to be subject to posttranslational modification such as N-glycosylation and disulfide bond formation, which are critical for protein folding, stability, and functionality (Gomord and Faye, 2004). In addition, targeting of recombinant proteins to the ER significantly improved production yields in plants (Schouten et al, 1996;Nausch et al, 2012;Kang et al, 2018). Therefore, we first determined whether bdSENP1 was capable of cleaving its substrate in the ER in vivo.…”
Section: Results Bdsenp1 Cleaves the Bdsumo Cleavage Site In Recombinmentioning
confidence: 99%
“…Moreover, the fusion of fungal hydrophobins (HFBI) (Gutiérrez et al, 2013) and the prolinerich domain of g-zein (Conley et al, 2011), a maize seed storage protein, increase the accumulation of recombinant proteins in plants. Fusions of an N-glycosylation domain (M domain) derived from human CD45 to either the C-or N-terminus (Kang et al, 2018), and of SBA, a sugar-binding lectin from soybean (Alqazlan et al, 2019), have also recently been shown to greatly enhance expression of fusion proteins in plants.…”
Section: Introductionmentioning
confidence: 99%